THE INCIDENCE AND QUALITY OF FINANCIAL GRAPHICS IN INDONESIAN IPO PROSPECTUSES - Dezie L. Warganegara; Yanthi R.I. Hutagaol; Tjut F. Bachrumsyah (University of Merdeka Malang, 2013)
The purpose of this study was to investigate the selectivity and the quality of financial graphs in IndonesianIPO prospectuses. The first hypothesis of this study related to the intensiveness in the use of the graphs with theprofitability of the IPO firms, while the second hypothesis associated the distortion in the graphs constructionswith the intention to show financial performance in a more favorable way. Content analysis was used toinvestigate the relationship between the intensiveness in the use of the graphs and the profitability. Thedistortion in the graphs constructions was detected using the Relative Graph Discrepancy (RGD) index. Thisstudy found that there was no evidence more profitable firms using graphs more intensively in their IPOprospectuses. With regards to distortion, it was found that IPO firms tended to exaggerate their performancedepicted on the financial graphs in their prospectuses.